Current Challenges in the Management of Chronic Pelvic Pain in Women: From Bench to Bedside - Siqueira-Campos VM; de Deus MSC; Poli-Neto OB; Rosa-; de Deus JM; Conde DM (Dove Medical Press, 2022)
Vânia Meira Siqueira-Campos,1 Mariana Siqueira Campos de Deus,1 Omero Benedicto Poli-Neto,2,3 Julio Cesar Rosa-e-Silva,3 José Miguel de Deus,1 Délio Marques Conde1 1Department of Obstetrics and Gynecology, School of Medicine, Federal University of Goiás, Goiânia, Goiás, Brazil; 2Laboratory for Translational Data Science, Ribeirão Preto Medical School, University of São Paulo, Ribeirão Preto, São Paulo, Brazil; 3Department of Obstetrics and Gynecology, Ribeirão Preto Medical School, University of São Paulo, Ribeirão Preto, São Paulo, BrazilCorrespondence: Délio Marques Conde, Department of Obstetrics and Gynecology, School of Medicine, Federal University of Goiás, Rua 235 S/N, Setor Leste Universitário, Goiânia, 74605-050, Goiás, Brazil, Tel +55 62 3209 6151, Email delioconde@gmail.comAbstract: Chronic pelvic pain (CPP) affects a significant proportion of women worldwide And has a negative impact on several aspects of these women's lives including mental health, work, relationships and sexual function, among others. This set of factors ultimately reflects negatively on quality Of life. The physiopathology of CPP is complex and remains to be fully clarified; however, recent advances have increased understanding of the mechanisms involved in chronic pain in general, and more specifically, CPP. Nonetheless, even when a detailed clinical history is obtained, meticulous physical examination is performed and imaging resources are appropriately used, the organic cause of the pain may still fail to be identified in a substantial number of women with CPP. Management of CPP may therefore be challenging. This narrative review was aimed at adding to the available literature on the subject, presenting and discussing the principal characteristics of CPP in women. The paper highlights gaps in the literature while providing the most up-to-date evidence associated with the physiopathology and classification of pain, its diagnosis and treatment. In addition, current challenges in the management of women with CPP are discussed.Keywords: central sensitization, chronic pain, neuropathic pain, nociplastic pain, pain neuroscience education